Post-LASIK dry eye disease: A comprehensive review of management and current treatment options - Tamimi, Atena; Sheikhzadeh, Farzad; Ezabadi, Sajjad Ghane; Islampanah, Muhammad; Parhiz, Peyman; Fathabadi, Amirhossein; Poudineh, Mohadeseh; Khanjani, Zahra; Pourmontaseri, Hossein; Orandi, Shirin; Mehrabani, Reyhaneh; Rahmanian, Mohammad; et al. (Frontiers in Medicine, 2023)
Laser-assisted in situ keratomileusis (LASIK) is a unique corneal stromal laser ablation method that uses an excimer laser to reach beneath corneal dome-shaped tissues. In contrast, surface ablation methods, such as photorefractive keratectomy, include removing epithelium and cutting off the Bowman’s layer and the stromal tissue of the anterior corneal surface. Dry eye disease (DED) is the most common complication after LASIK. DED is a typical multi-factor disorder of the tear function and ocular surface that occurs when the eyes fail to produce efficient or adequate volumes of tears to moisturize the eyes. DED influences quality of life and visual perception, as symptoms often interfere with daily activities such as reading, writing, or using video display monitors. Generally, DED brings about discomfort, symptoms of visual disturbance, focal or global tear film instability with possible harm to the ocular surface, the increased osmolarity of the tear film, and subacute inflammation of the ocular surface. Almost all patients develop a degree of dryness in the postoperative period. Detection of preoperative DED and committed examination and treatment in the preoperative period, and continuing treatments postoperatively lead to rapid healing, fewer complications, and improved visual outcomes. To improve patient comfort and surgical outcomes, early treatment is required. Therefore, in this study, we aim to comprehensively review studies on the management and current treatment options for post-LASIK DED.